2007
DOI: 10.1177/1538574407299601
|View full text |Cite
|
Sign up to set email alerts
|

Arteriography in the Delayed Evaluation of Wartime Extremity Injuries

Abstract: Recent combat casualties have stimulated a reassessment of the principles of management of high-risk extremity injuries with a normal vascular examination. Rapid evacuations have presented numerous U.S. soldiers to our service for evaluation in the early postinjury period. The objective of this single-institution report is to analyze the application of liberal arteriography in the delayed evaluation of modern wartime extremity injuries. Data from consecutive wartime evacuees evaluated for extremity injuries be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…Forward endovascular management at MTFs mimics the practice observed in civilian medicine, in which endovascular approaches are increasingly common and have been shown to provide improved survival and lower complication rates in certain situations. 22,23,[29][30][31] Johnson et al 31 reported finding an additional vascular injury in more than half (53%) of patients who had sustained a combat-related vascular injury by liberally using angiography after evacuation to the United States; 50% required surgical repair. In another review of injury patterns between 2001 and 2004 by Fox et al, 19 the most common indication for arteriography was mechanism of injury (42%), followed by abnormal examination finding (33%), operative planning (18%), or evaluation of a repair (7%).…”
Section: Discussionmentioning
confidence: 99%
“…Forward endovascular management at MTFs mimics the practice observed in civilian medicine, in which endovascular approaches are increasingly common and have been shown to provide improved survival and lower complication rates in certain situations. 22,23,[29][30][31] Johnson et al 31 reported finding an additional vascular injury in more than half (53%) of patients who had sustained a combat-related vascular injury by liberally using angiography after evacuation to the United States; 50% required surgical repair. In another review of injury patterns between 2001 and 2004 by Fox et al, 19 the most common indication for arteriography was mechanism of injury (42%), followed by abnormal examination finding (33%), operative planning (18%), or evaluation of a repair (7%).…”
Section: Discussionmentioning
confidence: 99%
“…The delay from injury to stateside evacuation has consistently been about 8 days. 19,20 It should be pointed out that a majority of our indications were therapeutic, meaning a DVT or PE may not have developed or manifested themselves early in the first week. Further, rapid mass casualty evacuations can lead to situations where injuries are initially missed and/or subsequently develop.…”
Section: Discussionmentioning
confidence: 97%
“…10,11 At a median of 6 days from injury to evaluation, Johnson et al found that the physical examination had a sensitivity of 38%, specificity of 90%, positive predictive value of 85%, and a negative predictive value of 51%. A normal physical examination did not accurately predict post-traumatic extremity arterial injuries sustained in combat, and the authors recommended liberal use of CTA and/or arteriography to assess for delayed or occult arterial injures.…”
Section: Discussionmentioning
confidence: 99%